Pengaruh Tingkat Kemiskinan Dan Harapan Lama Sekolah Terhadap PDRB Di Provinsi Bengkulu - Saputra, Andi; Samsuddin, M. Afdal (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2025)
This study aims to evaluate the influence of poverty levels and expected years of schooling on the Gross Regional Domestic Product (GRDP) in Bengkulu Province. Using secondary data from the Central Bureau of Statistics (BPS) and applying a linear regression approach, a series of classical assumption tests were conducted to ensure the model’s reliability. The results indicate no issues of multicollinearity or heteroscedasticity; however, autocorrelation and non-normality of residuals were detected. Overall, both independent variables were found to significantly affect GRDP. These findings suggest that regional economic development strategies should prioritize poverty reduction and improvements in education quality.